Assessment of Pulmonary Fibrogenic Potential of Multiwalled Carbon Nanotubes in Human Lung Cells. (31st May 2012) - Mishra, Anurag; Rojanasakul, Yon; Chen, Bean T.; Castranova, Vincent; Mercer, Robert R.; Wang, Liying
Abstract : Multiwalled carbon nanotubes have been shown to possess unusual fibrogenic activity in vivo and are currently the focus of intense toxicological investigations. This study further determines the fibrogenic potential of well-dispersed MWCNT in human lung cell culture models and to develop a novel platform for understanding the cellular mechanisms of MWCNT-induced lung fibrosis. Survanta, a natural lung surfactant, showed effectiveness in dispersing agglomerates of MWCNT to fine structures similar in size to aerosolized one. At relevant low doses (0.002–0.2  μ g/cm 2 ), MWCNT exhibited a dose-dependent bio-effect on the human lung epithelial cells which is more pronounced in dispersed-MWCNT compared to non-dispersed form. Significantly elevated levels of fibrogenic mediators, such as transforming growth factor- β 1 and matrix metalloprotienases-9 were observed in the dispersed-MWCNT treated lung epithelial cells. Based on previous in vivo studies showing that dispersed-MWCNT penetrated the interstitium and caused rapid interstitial fibrosis, we evaluated the potential direct interaction between lung fibroblasts and MWCNT. Direct stimulation of human lung fibroblast cell proliferation, collagen expression and fibroblast growth factor-2 were observed which suggests novel mechanisms of MWCNT-induced lung fibrosis. Our results indicate that the dispersion status of MWCNT determines their fibrogenic activity which is consistent with in vivo findings.